ANALISIS PENGARUH RETURN ON ASSET, BOPO, DAN SUKU BUNGA TERHADAP TINGKAT BAGI HASIL DEPOSITO MUDHARABAH PADA BANK UMUM SYARIAH - Andri Isna Kunti; Kunti Sunaryo (Jurnal Ekonomi Dan Bisnis, 2015)
This study aims to analyze the effect of Return on Asset (ROA), BOPO, and interest rate to the the levelof profit sharing mudharabah deposits.The population in this study is a Islamic bank in Indonesia. The population of this study were 11 Islamicbanks and the total sample of 3 banks. In purposive sampling using random sampling with criteria ofIslamic Banks serving quarterly financial statements in the year 2009-2011.The analysis techniqueused in this study is multiple linear regression to obtain a comprehensive picture of the relationshipbetween variables that one with the other variables. In addition, the hypothesis test used was the tteststatistic for testing the partial regression coefficient and test F-statistic for testing significancetogether with the significance level of 5%. Classic assumption test covering normality test,multicollinearity, heteroscedasticity test, and the autocorrelation test is also used in this study.The results of this study indicate that ROA, BOPO, and Interest Rates simultaneously have significanteffect on the level of profit sharing mudharabah deposits with significant > 5%, ROA is partially havesignificant negative effect on the level of profit sharing mudharabah deposits with significant 0.018,and Interest Rate partial effect have significant positive  effect with a significant of 0.013, while thepartial BOPO have’t sigifiat effet o the level of profit sharig udaraa deposits. Keywords : Return on Assets (ROA), BOPO, Interest Rate, Profit Sharing